Crises in Russia contemporary management policy and practice from a historical perspective - Porfirʹev, B. N. (Boris Nikolaevich); Simons, Greg (Routledge, 2016)
This unique book explores the problems of the national crisis management system in Russia, a country undergoing political, social and economic transition and one which is also prone to natural and man-made disasters. In detailing policy, institutional and legal issues and illustrating a number of case studies, the authors offer new ways of resolving the effects of disasters as well as increasing resilience by improving our understanding of the risks and vulnerabilities. In the book six chapters offer case studies of various types of disaster written in a unique collaboration between Russian scientists, Russian policy makers and Swedish scholars. Other chapters relate the role of mass media in Russian society and policy development. Taken together the book details changes in a crisis management system, policy and approach in a country that has undergone rapid fundamental political economic and social change.